Psychosocial Impact on Families during the COVID-19 Pandemic: A Scoping Review - Nadya Karlina Megananda; Heni Dwi Windarwati; Lilik Zuhriyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: COVID-19 pandemic did not only give rise disorder on COVID-19 confirmed patients, but also the patients’ family, thus it brought various psychosocial impacts. Objective: This article was aimed to explain psychosocial impacts on family during pandemic of COVID-19. Methods: This article used systematic review method through scientific article identification on four databases: PubMed, ProQuest, Ebsco, ScienceDirect in 2019-2021. The articles were selected through PRISMA based on both inclusion and exclusion criteria determined. The next step was analysis and result determination. The last step was consultation to experts of mental health. Results: Psychosocial impacts that appeared on family due to pandemic of COVID-19, for instance sleep disorder, anxiety, need for an increased social support, financial toxicity, lack of food supply, abandonment, depression, lonesome, mourning, post-traumatic stress, isolation, anticipative grief, worry, fear, stigma, discrimination, anger, stress transmission, risk of family welfare disturbance, confusion, parenting stress and domestic violence. The form of intervention that could be given to family such as cooperation with health service, health education, virtual social support, public complaint, maintenance of physical health, involvement among family members, limitation of information and mental health therapy. Conclusion: Identification of the family as an at-risk group could trigger mental health services to understand more about causes and consequences of psychological morbidity on this group of people.Abstrak: Pendahuluan: Pandemi COVID-19 tidak hanya menimbulkan gangguan pada pasien yang terkonfirmasi positif COVID-19 namun juga terjadi pada keluarga sehingga menimbulkan berbagai dampak psikososial. Tujuan: Artikel ini bertujuan untuk memaparkan dampak psikososial pada keluarga saat pandemi COVID-19. Metode: Metode yang digunakan pada artikel ini adalah sistematika review dengan melakukan identifikasi artikel ilmiah pada empat database yaitu Pubmed, ProQuest, Ebsco, ScienceDirect tahun 2019-2021. Artikel diseleksi dengan PRISMA berdasarkan kriteria inklusi dan ekslusi yang ditetapkan. Tahap selanjutnya yaitu analisis dan menetapkan hasil. Tahap terakir melakukan konsultasi kepada pakar kesehatan jiwa. Hasil: Dampak psikososial yang muncul pada keluarga akibat pandemi COVID-19 antara lain adalah gangguan tidur, kecemasan, kebutuhan peningkatan dukungan social, toksisitas financial, kekurangan pasokan makanan, pengabaian, depresi, kesepian, berduka, stress pasca trauma, pemisahan, kesedihan antisipatif, kekhawatiran, ketakutan, stigma, diskriminasi, marah, penularan stress, resiko gangguan kesejahteraan keluarga, kebingungan, stress pengasuhan dan kekerasan dalam rumah tangga. Intervensi yang dapat diberikan pada keluarga meliputi kerjasama dengan pelayanan kesehatan, pendidikan kesehatan, dukungan social melalui virtual, aduan masyarakat, menjaga kesehatan fisik, keterlibatan antar sesama anggota keluarga, pembatasan informasi dan terapi kesehatan jiwa. Kesimpulan: Identifikasi keluarga sebagai kelompok berisiko dapat memicu layanan kesehatan jiwa untuk lebih memahami penyebab dan konsekuensi morbiditas psikologis pada kelompok ini.